Strategi Pencitraan Lembaga Pendidikan Islam Anak Usia Dini : Studi Kasus RA Mu’adz bin Jabal Yogyakarta - Suyadi, Suyadi (Al-Athfal: Jurnal Pendidikan Anak, 2015)
The purpose of this research are (1) described how the concept of marketing (marketing concept) the institution islamic education early childhood unseeded in yogyakarta, and (2) described how islamic education institutions early childhood unseeded in yogyakarta do strategy positioning, differentiation, and branding in marketing school .Methods used in this report is written with a qualitative methodology with the approach phenomenology, that is trying to described the phenomenon how the concept of marketing (marketing concept) the institution islamic education early childhood creative (seed) in yogyakarta in doing strategy positioning, differentiation, and branding in marketing school. Conclusion this research is that imagery and credibility an institution will hold for long if always realized, maintaining and develop a range of good condition of time to time. Their ability take positioning, differentiation, and branding perhaps is power of accelerate.